1987
DOI: 10.1002/j.1460-2075.1987.tb04868.x
|View full text |Cite
|
Sign up to set email alerts
|

Base sequence-specific interactions of operator DNA fragments with the lambda-cro repressor coupled with changes in their conformations.

Abstract: The mechanism of interaction of the operator DNA with the lambda‐cro repressor protein was investigated using proton n.m.r. and photo CIDNP. Three kinds of DNA duplexes, the lambda‐OR3 17‐mer, phi80‐OR2 19‐mer and CRP binding site 22‐mer, were prepared, and all of their imino proton resonances of the complexes with lambda‐cro were assigned to individual base pairs. By monitoring the assigned signals of the DNA fragments and lambda‐cro, it was found that in the complex of lambda‐cro with lambda‐OR3, two subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In particular, DNA-induced changes have been observed in backbone 15 N and 1 H chemical shifts 23 and methyl 1 H shifts 24 in the region of residues 40-53, which includes strand β2 and part of β3 but does not directly contact DNA. The direction of the changes in backbone shifts was interpreted to suggest that the β2-β3 strand interaction tightens upon DNA complexation, while the β1-β2 interaction loosens.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, DNA-induced changes have been observed in backbone 15 N and 1 H chemical shifts 23 and methyl 1 H shifts 24 in the region of residues 40-53, which includes strand β2 and part of β3 but does not directly contact DNA. The direction of the changes in backbone shifts was interpreted to suggest that the β2-β3 strand interaction tightens upon DNA complexation, while the β1-β2 interaction loosens.…”
Section: Discussionmentioning
confidence: 97%
“…Within the same region, the photochemically induced dynamic nuclear polarization behavior of Tyr51 is also affected by specific DNA binding to O R 3. 24 Interestingly, the photochemically induced dynamic nuclear polarization changes were not observed upon binding of a disulfide-bonded Cro variant in the β-sheet region (V55C), putatively because the disulfide bond inhibited the induced-fit changes observed in the wild type. 25 Taken as a whole, the above NMR studies do suggest some alteration of the β-sheet framework of λ Cro upon specific DNA binding, but the nature and extent of these changes are not clear and might well prove rather subtle.…”
Section: Discussionmentioning
confidence: 98%
“…This large quaternary change induced by DNA binding is accomplished primarily by a twisting in the vicinity of residues 52-54 within the P-sheet strands that connect one Cro monomer with another. Chemical modification (26) and NMR (24,27) studies also show evidence for conformational changes in the vicinity of residues 52-54, including increased solvent accessibility of Tyr-51 and an increase in the exchange rate of the amide of Lys-56 upon specific DNA binding.…”
Section: Protein Conformationmentioning
confidence: 96%
“…This is about 2.9 A less than would be anticipated for straight B-DNA. NMR studies of Cro-OR3 complexes (22)(23)(24) have indicated bending or distortion near the center of the DNA and theoretical calculations (25) suggest that electrostatic interactions favor Cro binding to a bent form of DNA.…”
Section: Dna Conformationmentioning
confidence: 99%
“…The region of maximal sequence homology is found within a 20 residue sequence that aligns with the a2 and a3 helices of lcI, lCro and P22. 27,28,30 The f105 genome was searched for sequences that are closely related to the 14 bp-core region. A consensus sequence template was determined using the core sequences in O R 1, O R 2, O R 3, O R 4, O R 5 and O R 6.…”
Section: Sequence Analysis Of Mtcf105 and Orf4mentioning
confidence: 99%